Operations Management - Emerging Trend in the Digital Era 2021
DOI: 10.5772/intechopen.92706
|View full text |Cite
|
Sign up to set email alerts
|

A Modern Approach for Maintenance Prioritization of Medical Equipment

Abstract: Maintenance is a crucial topic in the life cycle management of medical equipment. Evidence-based maintenance consists of continuous monitoring of equipment performance, starting from evidence—the current state from the point of view of fault history—and improving its efficiency through the necessary modifications. This process is very important for optimizing the use and allocation of the resources available by the clinical engineering departments. Maintenance of medical equipment consists of two basic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…According to the World Health Organisation (WHO), initial expenses, and operating expenditures are two categories of required financial resources in maintaining medical equipment ( 35 ). Corciova et al ( 36 ) added that maintenance expenses represent a significant portion of the entire healthcare system which required 15–60% of the total cost to operate. Improper maintenance may affect performance and safety which greatly gave significant impact on the expenditure of healthcare institutions ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the World Health Organisation (WHO), initial expenses, and operating expenditures are two categories of required financial resources in maintaining medical equipment ( 35 ). Corciova et al ( 36 ) added that maintenance expenses represent a significant portion of the entire healthcare system which required 15–60% of the total cost to operate. Improper maintenance may affect performance and safety which greatly gave significant impact on the expenditure of healthcare institutions ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…The combination of 16 novel features, which are ( 1 ) age, ( 2 ) function, ( 3 ) PM status, ( 4 ) missed PPM, ( 5 ) maintenance requirement, ( 6 ) maintenance complexity, ( 7 ) downtime, ( 8 ) operations, ( 9 ) number of failures, ( 10 ) response time, ( 11 ) repair time, ( 12 ) backup and alternative unit, ( 13 ) maintenance cost, ( 14 ) asset status, ( 15 ) obsolescence, and ( 16 ) asset condition was used for prioritisation assessment and prediction of medical equipment's comprehensive strategic maintenance management. The system development measured 13,352 various types of medical equipment used in Malaysian public health clinic facilities.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organisation (WHO) divided the financial resources required for medical equipment maintenance into two categories: initial and operating expenditures ( 13 ). In addition, findings from Corciova et al ( 14 ), indicated that 15–60% of the entire healthcare system operation were used in maintenance expenditures. Bahreini et al ( 15 ) stated that unprofessional maintenance execution affected overall healthcare institutions' healthcare performance, safety, and expenses.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of a new medical device should account for the existing medical protocols, which should be kept in place. The integration of the equipment has multiple benefits: efficiency, easiness, familiarity, and easier maintenance, all of which lead to an increased adoption potential and thus contributes towards the clinical and commercial success of the equipment [ 42 ].…”
Section: Methodsmentioning
confidence: 99%